2018
DOI: 10.1097/md.0000000000011348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and mortality of congenital heart disease in Korean adults

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…1 ). 15 The overall 10-year SR for ACHD was higher in non-AF patients (87.5%) than in AF patients (69.7%) ( P < 0.001) ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…1 ). 15 The overall 10-year SR for ACHD was higher in non-AF patients (87.5%) than in AF patients (69.7%) ( P < 0.001) ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 91%
“…The prevalence and mortality were increased with aging in a Korean CHD study. 15 AF was more common in aging patients with CHD 20 21 and the incidence rate of AF in ACHD was higher for older age groups in Taiwan. 22 In our study, the mean age of the AF group was higher than that of the non-AF, and the proportion of AF became greater with aging in ACHD ( Table 2 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a previous investigation [9] it was reported that this trend derived from improvements in care, increasingly sensitive diagnostic tools, and increasing awareness of the potential relationships between common diseases and CHD. In our country, surgical mortality for CHD was relatively pretty low nowadays and the quality of imaging techniques is relatively so high [11].…”
Section: Discussionmentioning
confidence: 92%
“…Over the past two decades, the survival rate of patients with congenital heart disease (CHD) has markedly increased as a result of earlier diagnosis and advances in surgical and percutaneous interventions (Warnes, ). In the United States, up to approximately 90% of children with CHD are expected to survive into adulthood (Gurvitz et al, ), while the 10‐year survival rate for Korean adults with CHD has been reported to be as high as 92% (Jang et al, ). Despite these impressive developments, including increased survival rates and overall health status, psychosocial variables have been inadequately studied in the CHD population.…”
Section: Introductionmentioning
confidence: 99%